Amphibians Diversity in Sulap Hill and Watervang Dam, Lubuklinggau - Zico Fakhrur Rozi; Dian Samitra (Jurnal Biodjati, 2020)
Sulap Hill and Watervang Dam are located in the central of the city of Lubuklinggau, South Sumatra Province, which has a variety of organisms, including amphibians. This study aimed to determine the diversity of amphibian species in the area of  Sulap Hill and Watervang Dam Lubuklinggau City. This research was conducted from June to August 2018. Data collection was an exploration method-combined visual encounter survey (VES). The samples obtained were identified at the Biology Education Laboratory, STKIP PGRI Lubuklinggau. Data analysis included species composition, diversity index, and Evenness index, and conservation status. The results of the study found 5 families, consist of 11 species: Duttaphyrnus melanotictus, Ingerophrynus divergens, Phrynoidis asper, Fejervarya cancrivora, Fejervarya limnocharis, Limnonectes kuhlii, Limnonectes macrodon, Limnonectes paramacrodon, Polypedates leucomystax, Hylarana erythraea, Ichthyophis sumatranus. The results of the data analysis showed that the amphibian diversity index in the Sulap hill (1.55) and Watervang dam (1.84) was categorized as low. The Evenness index in Sulap Hill (0.86) and Watervang Dam (0.88) was categorized as a high uniformity and stable community. Based on data from the International Union for Conservation of Nature and Natural Resources (IUCN) Red List, 8 species have the status of Least Concern, 1 species with Vulnerable status, 1 species with Near-threatened status and 1 species with data deficient status.